A study on the anti-Helicobacter pylori activity of three medicinal plant crude extracts from Cannabis sativa, Mitragyna speciosa and Phyllanthus emblica - Khruethuen, S.; Pilasombut, P.; Woraprayote, W.; Janyaphisan, T.; Pumpuang, L.; Maniin, P.; Yahuafai, J.; Rumjuankiat, K. (My University, 2026)
In the present study, medicinal plant crude extracts were prepared from cannabis (Cannabis sativa), kratom (Mitragyna speciosa) and Indian gooseberry (Phyllanthus emblica) using four different solvents including ethanol, methanol, isopropanol, and water. The methanolic crude extracts had the highest weight and percentage yield, whereas the aqueous crude extracts exhibited the lowest values. The antimicrobial activity of these extracts against three Helicobacter pylori strains (ATCC 43504, 2888, and BK364) was evaluated using the spot-on-lawn method. The obtained results indicated that all medicinal plant crude extracts had an inhibitory effect against all tested H. pylori strains. The methanolic and ethanolic extracts of Cannabis sativa inhibited H. pylori strains ATCC 43504, 2888, and BK364 at the minimum inhibitory concentration (MIC) values ranging from 0.02-0.05 mg/mL. Additionally, a synergistic effect between Cannabis sativa, Mitragyna speciosa, and Phyllanthus emblica was investigated using the checkerboard assay. The synergistic interaction was observed between the Cannabis sativa, Mitragyna speciosa, and Phyllanthus emblica extracts, with a fractional inhibitory concentration index (FICI) of 2, indicating an indifferent effect when combined. Furthermore, the scanning electron microscopy (SEM) investigation revealed that the H. pylori cells were damaged after treatment with methanolic crude extracts of cannabis for 120 minutes.
Keywords: Helicobacter pylori; Medicinal plant crude extracts; Scanning electron microscopy; Synergistic effect